Irinotecan-containing doublet treatment versus irinotecan monotherapy as second-line choice for advanced gastric cancer - Yang, Liuting (BMC Gastroenterol, 2018)
BACKGROUND: For patients with advanced gastric cancer (AGC), second-line chemotherapy regimen remains controversial. The efficacy and safety of irinotecan-containing doublet treatment and irinotecan monotherapy were compared in this systematic analysis. METHODS: A search was conducted on EMBASE and Medline databases. All articles compared irinotecan-containing doublet to irinotecan as second-line chemotherapy for AGC. STATA statistical software (Version 12.0) was used to analyze the data. RESULTS: Seven studies, including 905 cases, were included in the analysis. Irinotecan-containing doublet treatment significantly prolonged progression-free survival compared to irinotecan monotherapy (HR = 0.82, 95% CI: 0.70–0.95). However, doublet treatment neither significantly prolong overall survival compared to monotherapy (HR = 0.94, 95% CI: 0.81–1.10), nor did it significantly increase the overall response rates and disease control rates, when compared to monotherapy. In addition, the irinotecan-containing doublet group had an increase in incidences of ≥ Grade 3 neutropenia (RR = 1.23, 95% CI: 1.01–1.51) and anemia (RR = 2.00, 95% CI: 1.37–2.92). CONCLUSIONS: When compared to irinotecan monotherapy, irinotecan-containing doublet treatment increased progression free survival and was tolerable as a second- line chemotherapy for AGC.